2009
DOI: 10.1038/bmt.2009.221
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal long-term physical performance in children and young adults after pediatric allo-SCT

Abstract: We present a set of tests for physical performance used for annual prospective follow-up after a pediatric transplant. Of the 103 eligible patients transplanted at a mean age of 8.8 years, 94 were included. The results were divided into early, performed 1 (n ¼ 46) or 2 (n ¼ 12) years post transplant, and late tests (n ¼ 66), performed 4-16 (mean 6) years post transplant. A total of 30 patients had tests both at early and late time points (paired tests). The control subjects included 522 healthy age-and genderm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
2
21
0
4
Order By: Relevance
“…In line with the report from Hovi et al, 28 we found higher exercise capacity in patients who participated in organized sports. This finding suggests that the children who participate in sports activity may achieve an improved rehabilitation compared with those who are physically less active.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In line with the report from Hovi et al, 28 we found higher exercise capacity in patients who participated in organized sports. This finding suggests that the children who participate in sports activity may achieve an improved rehabilitation compared with those who are physically less active.…”
Section: Discussionsupporting
confidence: 82%
“…Direct effects of chemotherapy and radiation, as well as indirect effects such as endocrine dysfunction, may contribute to this impairment. 1,28 Growth hormone deficiency was present in 11% of our patients. Although the mean height, weight and BMI z-scores of our patients were close to normal, the range was quite large, and VO 2peak was associated with patient BMI and height z-scores in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative management of joint contractures with physical therapy can improve outcomes in these children (Beredjiklian et al, 1998). In children following stem cell transplant, physical performance, as assessed with objective measures, is impaired in patients with extensive chronic GVHD (Hovi et al, 2010). Using these objective measures, carefully designed studies assessing the impact of physical therapy and exercise programmes on chronic GVHD should be feasible.…”
Section: Ancillary Therapies and Supportive Carementioning
confidence: 99%
“…Limitations in physical function have been reported for childhood HSCT survivors ranging from 7% (clinician report) 13 to 17% (selfreport) 14 and 40-62% from direct measures of cardiopulmonary fitness. 15 Associations between poor physical performance and cGVHD, cardiac conditions, immune suppression, treatment for secondary malignancies 16 and myeloid disease 17 have been found. Reports of psychological functioning are mixed.…”
Section: Introductionmentioning
confidence: 99%